Internalisasi Nilai-nilai Akhlak Melalui Program Monitoring - Marli Suhadi Pulungan (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This study is motivated by the continued presence of negative behaviors among students in various educational institutions, including general schools, madrasahs, and Islamic boarding schools, such as smoking, truancy, dating, and theft. Similar phenomena have also occurred at Al-Azhar Bi’Ibadillah Islamic Boarding School. However, this institution has sought to reduce such negative behaviors through the implementation of a mentoring program. Therefore, this study aims to examine the process of internalizing moral values through the mentoring program. The objectives of this study are to identify the moral conditions of male and female students, to analyze the stages of moral value internalization within the mentoring program, and to examine the challenges and efforts undertaken by murobbi and murobbiyah in internalizing moral values through the mentoring program. This research employs a qualitative method with a descriptive approach. Data sources consist of primary and secondary sources. The primary data were obtained from murobbi and murobbiyah, while the secondary data included the heads of Madrasah Aliyah and Madrasah Tsanawiyah, the foundation chairman, and Islamic Religious Education teachers. Data were collected through observation, interviews, and documentation studies. The findings indicate that the mentoring program effectively fosters students’ moral conduct toward Allah SWT, parents, teachers, oneself, peers, and the wider community. The internalization of moral values is carried out through several stages, namely value transformation, value transaction, transinternalization, and material deepening. The challenges encountered include limited facilities, insufficient teacher understanding, lack of cooperation, and students’ difficult-to-manage behavior. Efforts to address these challenges involve preventive, persuasive, cooperative, and repressive approaches, as well as the strengthening of religious education and Islamic spiritual development.